2021
DOI: 10.1021/jacsau.0c00091
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Assisted Hydrogenation of Carbon Monoxide to Methanol Using Molecular Manganese Catalysts

Abstract: Alcohol-assisted hydrogenation of carbon monoxide (CO) to methanol was achieved using homogeneous molecular complexes. The molecular manganese complex [Mn(CO) 2 Br[HN(C 2 H 4 P i Pr 2 ) 2 ]] ([HN(C 2 H 4 P i Pr 2 ) 2 ] = MACHO- i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…In line with the catalytic activity of Mn–MACHO complexes for CO hydrogenation, [12,16] 3 shows a high tolerance towards the presence of CO (Table 2, Entry 7). Even with additional 5 bar of CO, a high yield of methanol was obtained.…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…In line with the catalytic activity of Mn–MACHO complexes for CO hydrogenation, [12,16] 3 shows a high tolerance towards the presence of CO (Table 2, Entry 7). Even with additional 5 bar of CO, a high yield of methanol was obtained.…”
Section: Methodssupporting
confidence: 61%
“…Most recently, we found that complex 1 was highly active for the hydrogenation of carbon monoxide (CO) to methanol [12] . The reaction proceeds via formate ester intermediates formed under the basic reaction conditions from ROH and CO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the Leitner group reported the alcohol assisted CO reduction to methanol using the Mn pincer complex ( Mn2 ) resulting in a TON of 4023 and a TOF of 857 h –1 in EtOH/toluene as solvent under p (CO/H 2 ) = 5/50 bar at 150 °C ( Scheme 61 b). 393 …”
Section: Methanol Economymentioning
confidence: 99%
“…In contrast, catalytic reduction of CO by molecular catalysts is much less developed, which hinders the development of tandem processes that utilize CO as an intermediate. Some molecular complexes have been reported to catalytically reduce CO via hydrogenation, electrocatalysis, , or photocatalysis; , unfortunately, these catalysts typically require harsh reaction conditions and afford low conversion.…”
Section: Introductionmentioning
confidence: 99%